Ārvalstu tiešās investīcijas kā ekonomiskās izaugsmes faktors - Drare, Indra (Latvijas Universitāte, 2012)
Bakalaura darbā „Ārvalstu tiešās investīcijas kā ekonomiskās izaugsmes faktors” ir analizēta ārvalstu tiešo investīciju ietekme uz ekonomisko izaugsmi, un novērtēts, vai tas var būt par dzinuli vispārējai izaugsmei. Darbā izmantotas neoklasiskā Solova-Svana izaugsmes teorijas idejas, kuras ir piemērojamas attīstības valstu ekonomiskām, kāda ir arī Latvijā un vairumā Austurmeiropas valstu, un Koba-Duglasa ražošanas funkcija kvantitatīvajai analīzei. Darbā apskatīta investīciju struktūra un nozares, kurās tās ieplūst, investīciju vide, inovācijas un tehnoloģiju difūziju kā ĀTI ietekmes efektus, cilvēkkapitāla ietekme uz ekonomisko attīstību. Pēdējā nodaļā izvērsti aprakstīti un izanalizēti modeļi un empīriskās sakarības, kuros ir ietverti tādi rādītāji kā IKP un ĀTI, lietojot mazāko kvadrātu metodi lineārai regresijai, sevišķu uzmanību pievēršot ražošanas funkcijai. Izpētē tika izmantoti CSP, EUROSTAT, UNDP, OECD, LCB datubāzes, grāmatas par ekonomisko izaugsmi, makroekonomiku, ekonometriju, zinātniskie raksti par ĀTI. Kvantitatīvi analītiskajā daļā pielietoti vienības saknes testi, modificēto mazāko kvadrātu metode lineārai regresijai. Aprakstošajā analīzē ir ieskats metodoloģijā, kas saistās ar ĀTI. Analīzei tika izmantotas datorprogrammas Stata, Eviews, SPSS. Darbam ir 61 lappuse, 2 tabulas, 17 attēli, 8 pielikumi, 31 informācijas avots. Pētāmais laika periods: no 2000. līdz 2011. gadam ĀRVALSTU TIEŠĀS INVESTĪCIJAS, EKONOMISKĀ IZAUGSME, TEHNOLOĢIJU DIFŪZIJA, NEOKLASISKĀ IZAUGSMES TEORIJA

In the Bachelor thesis „Foreign direct investments as a source of economic growth” are analised direct investment effects on economic growth, and described if it can be a source of econoic growth. In the study there are used some ideas of economic growth and Solow - Swan model, that can be emplified on developing countries as well as Eastern European countries, and a Cobb – Douglas production function. There is also a description of investment structure and industries in Latvia, considered economic environment needed for a better investment opportunities like human capital, taxes, public goods. The last chapter focus on empirical regularities and some models with GDP and FDI. For the research were used databases like CSB, EUROSTAT, UNDP, OECD, LCB, some books about economic growth, econometrics, macroeconomics, publications about FDI. For analysis there are used unit root tests and fully modified ordinarary least squares. Paper is expanded in 61 pages, there are 2 tables, 17 images, 8 annexes, 31 information sources. Data research period: year 2000. – 2011. FOREIGN DIRECT INVESTMENTS, ECONOMIC GROWTH, TECHNOLOGY DIFFUSION, NEOCLASSICAL GROWTH MODEL ABSTRACT In the Bachelor thesis „Foreign direct investments as a source of economic growth” are analised direct investment effects on economic growth, and described if it can be a source of econoic growth. In the study there are used some ideas of economic growth and Solow - Swan model, that can be emplified on developing countries as well as Eastern European countries, and a Cobb – Douglas production function. There is also a description of investment structure and industries in Latvia, considered economic environment needed for a better investment opportunities like human capital, taxes, public goods. The last chapter focus on empirical regularities and some models with GDP and FDI. For the research were used databases like CSB, EUROSTAT, UNDP, OECD, LCB, some books about economic growth, econometrics, macroeconomics, publications about FDI. For analysis there are used unit root tests and fully modified ordinarary least squares. Paper is expanded in 61 pages, there are 2 tables, 17 images, 8 annexes, 31 information sources. Data research period: year 2000. – 2011. FOREIGN DIRECT INVESTMENTS, ECONOMIC GROWTH, TECHNOLOGY DIFFUSION, NEOCLASSICAL GROWTH MODEL ABSTRACT In the Bachelor thesis „Foreign direct investments as a source of economic growth” are analised direct investment effects on economic growth, and described if it can be a source of econoic growth. In the study there are used some ideas of economic growth and Solow - Swan model, that can be emplified on developing countries as well as Eastern European countries, and a Cobb – Douglas production function. There is also a description of investment structure and industries in Latvia, considered economic environment needed for a better investment opportunities like human capital, taxes, public goods. The last chapter focus on empirical regularities and some models with GDP and FDI. For the research were used databases like CSB, EUROSTAT, UNDP, OECD, LCB, some books about economic growth, econometrics, macroeconomics, publications about FDI. For analysis there are used unit root tests and fully modified ordinarary least squares. Paper is expanded in 61 pages, there are 2 tables, 17 images, 8 annexes, 31 information sources. Data research period: year 2000. – 2011. FOREIGN DIRECT INVESTMENTS, ECONOMIC GROWTH, TECHNOLOGY DIFFUSION, NEOCLASSICAL GROWTH MODEL
Foreign direct investments as a factor of economic growth
Keywords: Ekonomika